Aplikasi Pelayanan Jasa Laundry Berbasis WEB (Studi Kasus : Pelangi Laundry Kisaran) - Muhammad Yasin Simargolang; Nurmala Nasution ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - The development of the world in this millennium is very rapid, especially in the field of information technology. The level of speed and accuracy of information is a very big thing because it must be supported by technology adequate information. Similarly, the laundry business services, Pelangi Laundry is a business that runs a business in the field of laundry services. Based on the survey that has been conducted to date Rainbow Laundry does not have its own information system and still uses a manual system, this laundry also does not have an accurate database storage system so that all data is still stored in a book. Customers also do not get up-to-date information about the various laundry services offered and there are also customers who feel inconvenience when delivering even taking laundry that has been completed because they do not have much time to go to the laundry for reasons of being busy. To overcome these problems, an application will be designed that can help the Rainbow Laundry business so that this application can provide up-to-date information from Pelangi Laundry about laundry services offered to customers, provide fast and reliable laundry pick-up service to customers, facilitate the process of making income reports quickly, precisely and accurately, provide professional services to customers and minimize errors that may occur.Keywords - Application, Service, Laundry